Cardioprotective effect of cedrol in an inflammation systemic model induced by lipopolysaccharide: Biochemical and histological verification - Seyed Hamidreza Rastegar-Moghaddam; Sabiheh Amirahmadi; Mahsan Akbarian; Matin Sharizina; Farimah Beheshti; Arezoo Rajabian; Mohammad Hosein Eshaghi Ghalibaf; Mohaddeseh Azimi; Maryam Mahmoudabady; Mahmoud Hosseini (Journal of Cardiovascular and Thoracic Research)
Introduction: Evidence declared lipopolysaccharide (LPS) initiates inflammatory responses by stimulating the abandon of cytokines, which may perturb organ function. On the other side, it has been suggested Cedrol has potential properties, including anti-inflammatory and anti-oxidative activities. Herein, this study was done to assess the protective effect of Cedrol against LPS-associated heart damage. Methods: Thirty-five rats (200-250 g) were sorted into five groups, including control, LPS, LPS-Cedrol 7.5 mg/kg, LPS-Cedrol 15 mg/kg, and LPS-Cedrol 30 mg/kg groups. Cedrol was administrated through injected intra-peritoneally for two weeks. The heart tissues were removed and malondialdehyde (MDA) as a lipid peroxidation marker, superoxide dismutase (SOD), and catalase (CAT) as antioxidant markers were assessed. Furthermore, the interleukin (IL)-6 level in cardiac tissue was measured and Masson’s trichrome methods were employed to appraise cardiac inflammation and fibrosis, respectively. Results: Inflammation induced by LPS was significantly accompanied by myocardial fibrosis which was shown by Masson’s trichrome staining (P<0.001). In addition, LPS administration enhanced the MDA level while it diminished the activity of anti-oxidant markers such as CAT and SOD (P<0.001 for all cases). In the histological results, Cedrol improved LPS-induced inflammation and cardiac fibrosis (P<0.01 to P<0.001). Cedrol also enhanced CAT and SOD activities, whereas declined MDA level in the cardiac tissue (P<0.01 to P<0.001). Conclusion: The current findings proposed that the administration of Cedrol exerted a protective role in LPS-associated heart damage by reducing inflammation, cardiac fibrosis, and oxidative stress.